O cuidado à Síndrome da Imunodeficiência Adquirida na contemporaneidade: compreendendo o olhar de profissionais - Cleuma Sueli Santos Suto; Mirian Santos Paiva; Jeane Freitas de Oliveira; Andreia Silva Rodrigues; Daiane Santos Oliveira; Carlos Alberto Porcino (Universidade Federal do Ceará, 2017)
Objective: to understand the perspective of health professionals on care for people with acquired immunodeficiency syndrome. Methods: this is a qualitative approach based on the Social Representation Theory based on the free speeches of 73 practitioners from four specialized public services, which were submitted to Factorial Correspondence Analysis. Results: practitioners with longer training and working time have emphasized aspects related to the syndrome such as physical degradation, abandonment and death; practitioners with shorter training and working time have represented the care of the person living with human immunodeficiency virus as an increased knowledge of sensitivity, indicating attitudes and behaviors socially constructed and accepted as belonging to health practitioners. Conclusion: practitioners with more experience have seen the syndrome in its negative and initial aspect; the newcomers to the professional practice have shown sensitivity and openness to the relevant issues of this phenomenon and concrete possibilities of more effective/transforming care practices.